2018
DOI: 10.1097/ta.0000000000001891
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of endothelial phosphatidylserine exposure decreases ischemia-reperfusion induced changes in microvascular permeability

Abstract: Phosphatidylserine exposure is a key event in the pathogenesis of microvascular dysfunction during IRI. Clinically, inhibition of phosphatidylserine exposure is a promising strategy that may 1 day be used to mitigate the effects of IRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In our study, PS blockade was performed prior to the onset hemorrhagic shock. This timing has potential for therapeutic benefit by means of prophylactically blocking PS prior to an additional systemic insult or "second hit," such as damage control laparotomy 19 . Prior studies, including a phase II trial, have shown benefits of Diannexin when administered after an ischemic insult 19,23 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study, PS blockade was performed prior to the onset hemorrhagic shock. This timing has potential for therapeutic benefit by means of prophylactically blocking PS prior to an additional systemic insult or "second hit," such as damage control laparotomy 19 . Prior studies, including a phase II trial, have shown benefits of Diannexin when administered after an ischemic insult 19,23 .…”
Section: Discussionmentioning
confidence: 99%
“…This timing has potential for therapeutic benefit by means of prophylactically blocking PS prior to an additional systemic insult or "second hit," such as damage control laparotomy 19 . Prior studies, including a phase II trial, have shown benefits of Diannexin when administered after an ischemic insult 19,23 . Additionally, in murine models of ischemia reperfusion with Diannexin, reduction in renal tubule damage was apparent up to 8 days after ischemic insult, suggesting the benefits of PS blockade are durable 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reperfusion group ( n = 11) similarly underwent 60-min occlusion of the superior mesenteric artery and ligation of the marginal arteries. The occlusion was then released by declamping of the mesenteric artery, and reperfusion of the intestine was observed for 60 min without closing the abdomen[ 17 , 18 ]. The hydrogen group ( n = 9) was connected to the respiratory circuit using a gas supply hood that covered the face and head of the rats, in which spontaneous respiration was maintained without using mechanical ventilation[ 14 ].…”
Section: Methodsmentioning
confidence: 99%